Comparing the analytical performance of three SARS-CoV-2 molecular diagnostic assays (2020)
In December 2019, a novel coronavirus (SARS-CoV-2) was first isolated from Wuhan city, China and within three months, the global community was challenged with a devastating pandemic. The rapid spread of the virus challenged diagnostic laboratories to rapidly develop molecular diagnostic methods. As SARS CoV-2 assays became available for testing on existing molecular platforms, laboratories devoted unprecedented energy and resources into evaluating the analytical performance of the new tests and in some cases developed their own diagnostic assays under FDA-EUA guidance. This study compares the validation of three different molecular assays at the Johns Hopkins Molecular Virology laboratory: the RealStar® SARS-CoV-2 RT-PCR, ePlex® SARS-CoV-2, and the CDC COVID-19 RT-PCR tests. Overall, our studies indicate a comparable analytical performance of the three assays for the detection of SARS-CoV-2.